2020
DOI: 10.1177/0300060520928686
|View full text |Cite
|
Sign up to set email alerts
|

Digital psychotherapy as an effective and timely treatment option for depression and anxiety disorders: Implications for rural and remote practice

Abstract: Patients in regional, rural and remote communities experience perennial difficulties accessing mental health treatments in a timely manner, which contributes to inequitable outcomes when compared with their metropolitan counterparts. This situation frequently stems from a shortage of specialised face-to-face psychotherapy services available in local areas. The recent development of digital psychotherapy as an alternative treatment delivery method provides an opportunity to address this healthcare gap and to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…Clinicians are often reluctant to adopt tele–mental health because of concerns about the ability to establish a satisfying doctor–patient relationship and lack of knowledge of relevant privacy, transparency, and confidentiality issues [ 75 , 76 ]. A digital divide exists among patients, which excludes a large share of them from tele-mental health interventions [ 74 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians are often reluctant to adopt tele–mental health because of concerns about the ability to establish a satisfying doctor–patient relationship and lack of knowledge of relevant privacy, transparency, and confidentiality issues [ 75 , 76 ]. A digital divide exists among patients, which excludes a large share of them from tele-mental health interventions [ 74 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding satisfaction with the aftercare, the participants in the online aftercare groups indicated higher satisfaction values than the participants in the F2F group. This can be explained by the advantage of requiring less time for commuting to the therapist [ 8 ] and the absence of the fear of stigmatization in online therapies [ 15 ]. Further studies are required for a precise clarification.…”
Section: Discussionmentioning
confidence: 99%
“…This can overcome the problems with F2F therapies, which furthermore are often not readily available in all regions and where they are needed, resulting in patients promptly starting with their online intervention instead of waiting a long time (which is typical for F2F therapies due to limited availability of therapists [ 13 ]). Moreover, patients in psychotherapeutic interventions may miss their F2F sessions or drop out of therapy because they feel as if the location of the therapy is too far away [ 15 ]. Thus, online mental health interventions can bridge the gap between patients and therapists when the patient cannot travel to the intervention site (eg, [ 7 ]) or both are limited in their mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges and limitations related to the adoption of the reported interventions were common (55%) and greater heterogeneity is required given 45% of interventions were specific to China. A narrative review of digital psychotherapy found evidence of effectiveness for depression and anxiety disorders, of mild-to-moderate severity, from multiple randomized controlled trials and a large meta-analysis [67]. An online survey of the use of digital information and communication technologies in psychological counseling before and during a COVID-19 lockdown found overall positivity in the use of technologies and web-based interventions, with most practitioners noting approximately the same client involvement/adherence rates [68].…”
Section: Approachesmentioning
confidence: 99%